PENGERTIAN DAN FUNGSI PEMAHAMAN TINDAK PIDANA DALAM PENEGAKAN HUKUM DI INDONESIA - Putri, Rianda Prima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The function of criminal law can be divided into 2 (two) functions, namely: a) General: Criminal Law is part of the overall legal field, then the function of criminal law is also the same as the legal function in general is to regulate community life or organize in society ; and b) What is special: is to protect the legal interests of acts that want to rape them with sanctions in the form of criminal acts that are sharper when compared to sanctions contained in other branches of law. Intentional criminal law imposes suffering in maintaining recognized norms in law, this is why criminal law must be considered as ultimum remedium or the last drug, if sanctions or efforts in other legal branches do not work the new criminal law will take effect. In criminal sanctions there is something tragic (sad sorrow) so that the criminal law is said to be slicing its own flesh or as an edged sword.